AN INQUIRY INTO EFL LEARNERS PERCEPTIONS OF WHATSAPP FOR ORAL PEER ASSESSMENT - Ika Wulandari; Oikurema Purwati; Slamet Setiawan; Syafi'ul Anam (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2021)
The current global pandemic triggers English teachers to be innovative and competent in delivering teaching instructions in online classrooms. Even though Mobile-Assisted Language Learning (MALL) is widely used to support online language teaching and learning, nonetheless, the integration of Mobile-Assisted Language Assessment (MALA) in speaking skills has not been immensely examined. Thus, this current study aimed to scrutinize Indonesian EFL learners perceptions of the use of WhatsApp as a tool for peer assessment in an online speaking class, as well as its potential benefits and drawbacks. This qualitative study employed a semi-structured interview to gain the data which were then analyzed by using phenomenological analysis. Fourteen secondary learners participated in two sessions of an online class by assessing their peers oral performances via the WhatsApp application. In the end, they were interviewed regarding their views on the method employed to assess their oral skills. The results indicated the participants positive perceptions towards the method along with various benefits and drawbacks they encountered during the process which were divided into technical and academic aspects. The results suggested that WhatsApp as a tool for mobile-assisted language assessment was not supposed to be perceived as a single major assessment for speaking skills, rather as an alternative to complement traditional assessments.